Combination oral antithrombotic therapy for the treatment of myocardial infarction: recent developments. (3rd May 2018) - Tantry, Udaya S.; Navarese, Eliano P.; Myat, Aung; Chaudhary, Rahul; Gurbel, Paul A.
ABSTRACT: Introduction : There have been significant new developments in the treatment of patients with myocardial infarction with respect to oral antithrombotic agents over the past decade. Recent studies have explored the potential utility of targeting the dual pathway inhibition of platelet function with single or dual antiplatelet agents and the thrombin pathway with direct thrombin inhibitors or factor Xa inhibitors. Areas covered : In this review, the authors focus on the recent developments of oral antithrombotic agents including antiplatelet and antithrombin agents. It is based on literature covering: aspirin, P2Y12 receptor blockers, PAR-1 inhibitors, direct thrombin inhibitors and factor Xa inhibitors from PubMed since 2008. Expert opinion : Since thrombus formation involves multiple pathways including platelet activation and aggregation and coagulation, simultaneous and optimal blockade of these pathways is essential to prevent thrombotic complications and to avoid excessive bleeding in the myocardial infraction setting. Despite an improved anti-ischemic effect associated with potent P2Y12 inhibitors plus aspirin, the degree of adverse event reduction compared to clopidogrel therapy in large scale trials is modest along with significantly greater bleeding. Recent studies suggest that targeting the thrombin pathway in addition to antiplatelet agents in high risk patients may further mitigate the risk of ischemic event occurrences with improved safety profiles.